Detection of homologous plastic PET‐degrading enzyme‐encoding DNA from enriched plastic‐contaminated soil samples - Wulandari, Sri Rezeki; Sabbthini, Gabriela Christy; Trinugroho, Joko Pebrianto; Nurhayati, Niknik; Ulfah, Maria; Helianti, Is (Universitas Gadjah Mada, 2026)
Piscinibacter sakaiensis, first isolated in Japan, is the only well‐characterized bacterium known to possess both PETase and MHETase, enabling complete polyethylene terephthalate (PET) degradation. To date, no additional habitats for the species have been reported. This study aims to identify homologous PETase and MHETase DNA from plastic‐contaminated landfill soils in Indonesia. Enrichment cultures were established from soil samples collected at Galuga (Bogor) and Cipeucang (South Tangerang). PCR amplification and sequencing revealed a full‐length MHETase homolog (G2MHETase, 1,812 bp) from Galuga, showing 99.4% and 99.3% nucleotide identity to MHETase from P. sakaiensis and Delftia sp. respectively. The deduced amino acid sequence shared 98.5% identity with both. In contrast, a partial PETase homolog (502 bp of 873 bp) was amplified from the Cipeucang sample, displaying 96 and 93% amino acid identity to PETase from P. sakaiensis and P. gummiphilus respectively. Nanophore NGS analysis of bacterial diversity indicated distinct microbial community profiles between the two sites. Rare taxa potentially associated with the detected genes included P. gummiphilus, Delftia sp., Delftia tsuruhatensis and Xenophilus aerolatus from Galuga, and Piscinibacter and Acidovorax from Cipeucang. These findings demonstrate the feasibility of detecting homologous PET degrading enzyme genes from plastic‐contaminated soils using PCR‐based approaches.